2019
DOI: 10.1007/s13127-019-00390-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the evolution and terrestrialization of scorpions (Arachnida: Scorpiones) with rocks and clocks

Abstract: Scorpions (Arachnida: Scorpiones Koch, 1837) are an ancient chelicerate arthropod lineage characterised by distinctive subdivision of the opisthosoma and venomous toxicity. The crown group is represented by over 2400 extant species, and unambiguous fossil representatives are known at least from the Cretaceous Period. However, a number of extinct scorpion lineages existed in the Palaeozoic Era, many of which are of a contentious marine (or at least semi-aquatic) lifestyle, and have long caused confusion regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 95 publications
(116 reference statements)
1
16
0
Order By: Relevance
“…Our estimates encompassing a Late Ordovician median age for crown-group Opiliones corresponds to that estimated using tip dating by Sharma and Giribet (2014), whereas node calibration in that study recovered a Silurian median. In the case of Scorpiones, a Late Devonian to Carboniferous origin of the crown group is closely comparable to the date for the same node by Sharma et al (2018), but older than the strictly Carboniferous ages estimated by Howard et al (2019). However, in all cases mentioned the credibility intervals substantially overlap, indicating that these independent studies found results that, despite some differences, are not significantly different and corroborate each other.…”
Section: Molecular Divergence Time Estimationsupporting
confidence: 66%
“…Our estimates encompassing a Late Ordovician median age for crown-group Opiliones corresponds to that estimated using tip dating by Sharma and Giribet (2014), whereas node calibration in that study recovered a Silurian median. In the case of Scorpiones, a Late Devonian to Carboniferous origin of the crown group is closely comparable to the date for the same node by Sharma et al (2018), but older than the strictly Carboniferous ages estimated by Howard et al (2019). However, in all cases mentioned the credibility intervals substantially overlap, indicating that these independent studies found results that, despite some differences, are not significantly different and corroborate each other.…”
Section: Molecular Divergence Time Estimationsupporting
confidence: 66%
“…This is also supported by the notion that the oldest known arachnids, the Silurian scorpions, had compound lateral eyes 58,91–93 , while the lateral eyes of extant crown group scorpions consist of two to five pairs of lateral lenses 86 . Perhaps in relation to a ground-dwelling terrestrial life-style extant arachnids mostly seem to rely on non-visually sensory systems such as mechanoreceptors (trichobothria, pectines and highly sensitive setae) or chemosensory systems, which seem to be metabolically much less expensive than visual systems 94,95 ; so eyes may become reduced or disappear.…”
Section: Discussionmentioning
confidence: 69%
“…Also revealing is a specimen from the Lower Devonian Rhynie Chert of Scotland (~410 Mya, Palaeocharinus sp. ), which belongs to the Trigonotarbida, an extinct group of spider-like arachnids, and possibly closely related to scorpions 58 . It shows three larger lenses, and a horizontal row between them of 10–11 smaller facets - a system which may indicate a transition from the compound to a single-lens eye.…”
Section: The Eyes Of Mandibulates Arachnids and Horseshoe Crabsmentioning
confidence: 99%
“…originating during the late Carboniferous as in Hymenoptera (Ronquist et al, 2012) and Hemiptera (Misof et al, 2014)], or even ancient (i.e. Ordovician as in major splits among arachnid orders (Howard et al, 2019), and have proved successful in providing well-resolved and often strongly supported phylogenetic trees.…”
Section: Introductionmentioning
confidence: 99%